Алгоритм і програмне забезпечення для оцінки освоюваності позабалансових запасів нафти в малопродуктивних пластах - Лозинський, О.Є.; Лозинський, В.О. (Геоінформатика, 2016)
Розглянуто можливість освоєння забалансових запасів нафти в малопродуктивних пластах. Описано алгоритм і програмне забезпечення для оброблення і аналізу геолого-промислових даних за кривими падіння вибійного тиску під час багатоциклової дії на пласти зростаючими репресіями. Зазначено, що використання розробленої комп’ютерної технології може забезпечити накопичення, зберігання, оброблення і відтворення об’єктивної геолого-промислової інформації та прийняття обгрунтованого рішення про проведення заходів щодо збільшення продуктивності нафтоносних пластів, а в результаті – переведення забалансових запасів у зоні дренування свердловин у балансові та збільшення загального видобутку нафти на родовищі. Рассмотрена возможность освоения забалансовых запасов нефти в малопродуктивных пластах. Описаны алгоритм и программное обеспечение для обработки и анализа геолого-промысловых данных по кривым падения забойного давления при многоцикловом воздействии на пласты нарастающими репрессиями. Отмечено, что использование разработанной компьютерной технологии может обеспечить накопление, хранение, обработку, воспроизведение объективной геолого-промысловой информации и принятие обоснованного решения о проведении мероприятий по увеличению производительности нефтеносных пластов, а в итоге перевод забалансовых запасов в зоне дренирования скважин в балансовые и увеличение общей добычи нефти на месторождении. Purpose. The authors had a task to create an algorithm and an accessible for end customers modern computer program able to make decisions on the clarification of the geological factors which limit inflow of petroleum in the suspended wells draining off-balance stocks in productive layers; and to increase the productivity of layers.
Design/methodology/approach. To estimate prospects to increase the productivity of mining holes with the non-commercial inflow of petroleum due to additional channels of influx from layers in a mining hole, it is necessary to conduct experimental works to obtain information on the technological possibility of layers hydraulic fracturing depending on the possibility of a concrete mining hole size of pressure of liquid inflating; presence and size of changes in the hydraulic permeability of layers and near well bore at different values of supply pressure; the expected increase of the productivity of a mining hole while maintaining channels of filtration fixed at liquid inflating in the layers. It is feasible to obtain this information on condition the mining holes are studied by inflating liquid in to the layers with the gradual increase of supply pressure.
Findings. We suggest describing the drop of pressure at the well bore in multi-cycle research with an equation connecting pressure at the moment of closing the mining hole to register drawdown pressure curve with a complex parameter which includes aggregated volume of liquid inflating in to the layers before the mining hole closing, time duration of liquid inflating in to layers, duration of time from the beginning of the liquid inflating in to layers to the moment of time after stopping the inflating, and the coefficient of hydraulic permeability of the layer in any loop of research.
Practical value/implications. The created method and computer technology can permit to accumulate, store, process and recreate objective geological information and to make grounded decisions on measures to increase the productivity of petroleum containing layers, and as a result, to move the off-balance sheet supplies in the areas of wells draining to the balance ones and increase the total production of petroleum of a deposit.